Reaping the reef: Provisioning services from coral reefs in Solomon Islands. (December 2015) - Albert, Joelle A.; Olds, Andrew D.; Albert, Simon; Cruz-Trinidad, Annabelle; Schwarz, Anne-Maree
Abstract: The marine biodiversity in the Coral Triangle sustains the livelihoods of roughly 100 million coastal people, yet this region is under threat from numerous local and global stressors. Regional actions underway to address coastal and marine degradation and an improve understanding of the social-ecological links between people and their environment. Economic assessments of coral reef provisioning services afforded to rural communities in Solomon Islands identified a diverse range of fisheries-based (fish, seaweed, clam, trochus, crayfish and shells) and coral-based (sand, rubble, stone, and corals for lime, aquarium and curio trades) products. Fisheries products (in particular reef fish) were important for both village subsistence and cash economies, providing the equivalent of US 5173 (±515) annually per respondent. In contrast, coral products contributed the equivalent of US 2213 (±396) annually per respondent, primarily to cash economies, particularly in study villages located in close proximity to national markets. Extractive coral activities have the potential to reduce reef resilience, diminish the viability of fisheries and so compromise the livelihoods of dependent communities. Improved management, legislative review and livelihood diversification strategies are likely to be required to manage coral reefs and the ecosystem services they provide across the Coral Triangle region. Graphical abstract: Highlights: Coral reefs provide a diverse range of provisioning services to rural communities. The value of reef provisioning services to households is 130% higher than income. Extraction of coral products for cash can undermine reef and community resilience.